PENCITRAAN PEMERINTAH DAERAH MELALUI MEDIA PADA BAGIAN HUMAS DI SEKRETARIAT DAERAH KABUPATEN POLEWALI MANDAR - Muhammad Abid (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2018)
This study aims to know how the imaging of the government is done through the media by the state of the public in the Polman Regional Secretariat. This research is a qualitative research that explains the phenomenon in depth, creates a description, systemally, accurately and facts about the facts, as well as describing the reality that is happening. The role of public relations as a communicator's that is helping the community to interaction and communication to the goverment. The role of public relations as relationships are relatively good relationships between the whole community with government agencies, through delivery of regional development information. The role of public relations in building the image of the Government of Polewali Mandar Regency to the public can be seen from information updates through the internet site.